면역억제에 의한 마우스의 Cryptosporidium 발현 실험 - 채종일(Jong-Yil Chai); 신손문(Son Moon Shin); 윤종구(Chong Ku Yun); 유재란(Jae-Ran Yu); 이순형(Soon-Hyung Lee) (Korean journal of parasitology, 1990)
Cryptosporidium, a coccidian parasite first described by Tyzzer (1907) from a laboratory mouse, has become an important human enteric pathogen causing overwhelming diarrhea especially in immunocompromised patients such as AIDS. This parasite has been reported from over 20 countries and is recognized as a cosmopolitan species. In Korea, however, thEre has been no report on human as well as animal cryptosporidiosis. This study was performed so as to verify the presence of Cryptosporidium in Korea by activating the parasite from laboratory mice by immunosuppression. Total 65 conventionally.bred ICR mice including a control (5 mice) and 3 experimental groups (20 each) were used for this study. Group I was immunosuppressed with Prednisolone injection (1 mg IM, every other day) for 7 weeks. Group II (prednisolone injection and tetracycline administration) and Group III. (prednisolone injection and trimethoprim-sulfamethoxazole administration) were prepared to observe the effect of antibacterial agents on the activation of cryptosporidiosis. In fecal examinations of mice Cryptosporidium oocysts($4-6{μm}$ in size) were detected from 1 week after the start of immunosuppression and the mice began to die. In H-E stained tissue sections of the lower jejunum, numerous very small ($2~4{\;}{μm}$), dense, ovoid or spherical, slightly basophilic bodies were seen attached on the free border of mucosal epithelial cells. In scanning and transmission electron microscopic observations, these organisms were identified as various developmental stages of Cryptosperidium. The species is considered to be C. parvum. Cryptosporidiosis was activated not only in Group I but also in Group II and III, indicating no protective effects of the antibacterial agents used, although the mice in Group II and III lived longer than those in Group I. The present study confirmed that Cryptosporidium exists in laboratory mice bred in Korea, and predicts possible occurrence of human cryptosporidiosis in Korea. 실험용 마우스(ICR)에 프레드니솔론을 주어 인공적으로 면역억제시키면서 Cryptosporidium 발현 여부를 7주 동안 관찰한 바 다음과 같은 결과를 얻었다. 면역 억제 1주 후부터 마우스 대변에서 Cryptosporidium의 Oocyst (크기 440 ㎛)가 검출되었고 2주 후부터 마우스가 사망하기 시작하였다. 대변에서 oocyst가 검출된 마우스의 소장 절편을 H&E 염색하여 광학현미경으로 관찰한 결과 Cryptosporisium은 공장 하부에서 호발하였으며 장 융모의 점막 상피세포 표면에 점같이 붙은 모습으로 무수히 발견되었고 호염기성이었으며 크기는 직경 2∼4 ㎛정도 되었다. 이들의 여러 발육 단계에 대해 주사 전자현미경 및 투과 전자현미경으로 입체구조를 관찰하였으며 그 결과 충체의 종은 C. Parvum으로 동정하였다. 항균제(tetracycline, trimethoprim-sulfamethoxazole)를 면역억제제와 함께 투여한 실험군에서도 Cryptosporidium이 발현되었으나 면역 억제제만을 투여한 실험군의 마우스보다 수명을 다소 연장시킬 수 있었다. 이 실험 결과 우리 나라에도 Cryptosporidium(C. Parvum)이 존재하고 있음을 확인하였으며 인체 감염례가 있을 가능성을 짐작할 수 있었다.